2022
DOI: 10.1039/d2fo01389d
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, identification and characterization of taste peptides from fermented broad bean paste

Abstract: Pixian broad-bean paste (PBBP) is a famous fermented condiment in China, which may produce abundant flavor peptides during fermentation process. Herein, the tasteful peptides from fermented broad-bean (FB) were separated...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 43 publications
(54 reference statements)
3
30
0
Order By: Relevance
“…Flavor peptides mostly exhibit not a single taste but a comprehensive expression of a mixture of multiple flavors . Almost every peptide contains sweetness, which was similar to the conclusion of Li et al and Saites et al that umami-tasting substances could potentiate the perception of sweetness. , Sourness and astringence were detected in some synthetic peptide samples, which may come from the presence of those residual acidic amino acids during the synthesis of the target peptide. , Additionally, sensory panels were perceived to have a slightly salty taste. Among all peptides, NK-7, EK-12, and LR-5 possessed a strong umami taste, and DK-6 displayed a slight umami taste.…”
Section: Resultssupporting
confidence: 76%
See 4 more Smart Citations
“…Flavor peptides mostly exhibit not a single taste but a comprehensive expression of a mixture of multiple flavors . Almost every peptide contains sweetness, which was similar to the conclusion of Li et al and Saites et al that umami-tasting substances could potentiate the perception of sweetness. , Sourness and astringence were detected in some synthetic peptide samples, which may come from the presence of those residual acidic amino acids during the synthesis of the target peptide. , Additionally, sensory panels were perceived to have a slightly salty taste. Among all peptides, NK-7, EK-12, and LR-5 possessed a strong umami taste, and DK-6 displayed a slight umami taste.…”
Section: Resultssupporting
confidence: 76%
“…All of the peptides showed umami taste, and they were nontoxic with good water solubility and stability. Interestingly, we previously found that the umami peptides were mainly derived from Aspergillus oryzae and broad beans . However, in this study, the umami peptides were derived from the dominant microorganisms during the fermentation of broad beans, suggesting that food fermentation is an important process to produce umami peptides. , …”
Section: Resultsmentioning
confidence: 54%
See 3 more Smart Citations